2022
DOI: 10.3390/life12122117
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Cannabinoids and Their Applications in COVID-19 Treatment

Abstract: Cannabis sativa is one of the first medicinal plants used by humans. Its medical use remains controversial because it is a psychotropic drug whose use has been banned. Recently, however, some countries have approved its use, including for recreational and medical purposes, and have allowed the scientific study of its compounds. Cannabis is characterized by the production of special types of natural products called phytocannabinoids that are synthesized exclusively by this genus. Phytocannabinoids and endocanna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 139 publications
(177 reference statements)
0
9
0
Order By: Relevance
“…Recently, Rull et al (2023) [ 9 ] published a review of the history of C. sativa , and Schanknecht et al, (2023) [ 10 ] presented scientific evidence of the utilization of cannabis in the treatment of melanoma. Other review articles have reported on the impact of cannabinoids on the central nervous system, COVID-19 treatment, and the methodology of detection and quantification of cannabis phytochemicals, as published by Madden et al (2023), Pérez et al (2022), and Zhang et al (2022) [ 11 13 ]. Lately, some nations (USA, Canada, Morocco, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rull et al (2023) [ 9 ] published a review of the history of C. sativa , and Schanknecht et al, (2023) [ 10 ] presented scientific evidence of the utilization of cannabis in the treatment of melanoma. Other review articles have reported on the impact of cannabinoids on the central nervous system, COVID-19 treatment, and the methodology of detection and quantification of cannabis phytochemicals, as published by Madden et al (2023), Pérez et al (2022), and Zhang et al (2022) [ 11 13 ]. Lately, some nations (USA, Canada, Morocco, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Central receptor targets for the effects of CBD have been described. These include GRP55, TRPV1, CB2 ( Perez et al, 2022 ), and some recent work has identified actions via either 5HT1A or CB1 in hippocampus ( Franzen et al, 2023 ). Due to the lack of similar lasting effects of THC on network strength compared to CBD, a CB1 mediated action might be unlikely to mediate the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…CBD has medicinal benefits without the euphoric symptoms that THC is commonly associated with, it is frequently considered to be the more adaptable and advantageous of the two [66]. CBD, widely acknowledged for its potential therapeutic applications, finds use in treating diverse medical conditions, including epilepsy, anxiety, pain management, and inflammation [62,64]. An essential distinction lies in the fact that CBD does not induce intoxication, making it suitable for patients seeking relief without experiencing the psychoactive high associated with THC [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was noted that the advantages of combining THC with CBD might be more limited when treating focal-onset seizures [72]. Gaston et al (2017) stated that Δ9-THC may possess analgesic properties, rendering it advantageous for treating persistent pain syndromes [62]. Due to its antiemetic qualities, it can help reduce nausea and vomiting brought on by some medical procedures, like chemotherapy [63].…”
Section: δ9-tetrahydrocannabinol (Thc)mentioning
confidence: 99%